Nocardia species epidemiology and susceptibility profiles from 2019-2022 in South Africa - Dr Teena Thomas; Dr Michelle Lowe; Mrs Karren Le Roux; Dr Kathy-Anne Strydom (International Journal of Infectious Diseases)
Introduction: Nocardia species cause human infections, from localised to disseminated disease. It constitutes a public health threat due to the lack of sufficient information around this organism. In South Africa, the last publication on this organism was in 2010. Predominant species types and antibiotic susceptibilities would have changed over this period. As a result, this study aimed to address this knowledge gap. Methods: This was a retrospective, descriptive study. Data was collected retrospectively from the Central Data Warehouse of the National Health Laboratory Services on suspected Nocardia species from 01 Jan 2019- 31 Dec 2022. Organism speciation was performed using 16SrRNA sequencing and susceptibility testing by the broth microdilution method. Data analysis included patient age, sample types from which the organism was cultured, distribution in the various provinces, species types, species susceptibility profiles including record of bactrim non-susceptibility. Results: One hundred and sixty-five positive culture results were analysed from both public and private healthcare sectors. The majority of positive cultures (n=46) were from the 30-39 year age group. The organism was predominantly cultured from pus samples (n=51). The top two provinces with the highest culture positivity were Gauteng (n=114) and the Western Cape (n=30). Four isolates were not sequenced and 30 isolates lacked susceptibility results. Twenty-nine percent (n=47) of the Nocardia species that were sequenced could not be speciated. The top two species country-wide were N. abscessus complex (n=42) and N. cyriacigeorgica (n=29). Approximately ninety percent (n=121) of all isolates tested, were bactrim susceptible.Bactrim non-susceptibility was seen in three provinces, Western Cape, Kwa-Zulu Natal (KZN), and Gauteng. The implicated species, identified by sequencing, included N. kroppenstedtii (n=3), N. abscessus complex (n=2), N. cyriacigeorgica (n=2), N. brasiliensis (n=1), N. farcinica (n=1), N. pseudobrasiliensis (n=1), and N. nova complex (n=1). Discussion: The study spans a three-year period with data collected nationwide. It included a substantially larger number of clinical isolates from the last study. The ages most affected by infections correlates with the high HIV prevalence group in the country. The predominant isolation from pus suggests that majority were deep-seated infections. The Nocardia species types have changed over time and the susceptibility to antibiotics such as bactrim, amikacin, augmentin, ciprofloxacin, clarithromycin and imipenem is decreasing. The study findings also highlight the need for alternative methods for speciation of this organism.Study limitations included that risk factors for infection were not investigated and missing information was encountered due to the retrospective nature of the study. Conclusion: The study provides an updated perspective on Nocardia epidemiology and susceptibility patterns in South Africa. It highlights the need for closer surveillance based on the changing epidemiology observed over a 12-year period. In addition, alternate targets for speciation need to be investigated as a priority.